A strategy to alleviate poverty in the Matobo Hills World Heritage Site of Zimbabwe - Tendai Fortune Muringa; Paul Mupira; William Lungisani Chigidi (White Rose University Press, 2023)
World Heritage Sites (WHSs) are places of outstanding universal significance with a crucial role to perform in sustainable development (SD) particularly the aspect of eradicating poverty. As such WHSs are not only meant to serve global interests in tourism and conservation but have an additional mandate to meet the social and economic needs of local communities wallowing in poverty. Matobo Hills World Heritage Site (WHS) in southwestern Zimbabwe has potential to promote the SD Goal 1 (SDG1) which seeks to eradicate poverty in all its forms and dimensions by 2030. The idea of eradicating poverty is noble and in line with the global SD Agenda, but the question is on whether WHSs can fulfil this function. This paper assesses the possibilities and challenges of eradicating poverty in local communities around Matobo Hills WHS. It analyses the social and economic opportunities that Matobo Hills WHS presents and if at all these suffice to eradicate or ameliorate poverty. This research established that it is challenging for WHSs to eradicate poverty in its entirety in a community and in a nation. The multidimensional nature of poverty presents a wide array of aspects that include the socio-cultural, economic, political, and environmental aspects of human life which cannot be adequately addressed through use of a single WHS. As a result, the need to sustain the physical landscape of Matobo Hills WHS takes precedence over fulfilling the international obligations to eradicate poverty in its entirety. This paper therefore recommends that generalisations made at a global scale need to be weighed in at national and local levels to ascertain how much heritage can offer to the people in relation to eradicating poverty in Zimbabwe. This would ensure that efforts to eradicate poverty are realistically placed within the capacity of a given WHS.